2014
DOI: 10.1155/2014/347196
|View full text |Cite
|
Sign up to set email alerts
|

Flow of a Maxwell Fluid between Two Porous Disks Rotating about Noncoincident Axes

Abstract: This paper is concerned with the steady flow of a Maxwell fluid between two porous disks rotating with the same angular velocity about noncoincident axes normal to the disks. An exact solution to the problem depending on the Deborah number, the suction/injection velocity parameter, and the Reynolds number is obtained. It is shown that the core of fluid tends to rotate about the -axis that characterizes the line in equal distance to the two axes of rotation when the Deborah and Reynolds numbers increase and a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Besides the above authors, Ersoy has reported excellent results for different fluid flows induced by eccentric-concentric rotation of a disk and the fluid at infinity for both Newtonian (Ersoy 2003) and non-Newtonian fluids, e.g. second-grade fluid and Maxwell fluid (Ersoy 2010, 2014). Similar to the previous authors, Ersoy (2003, 2010, 2014) have also investigated these problems using the Laplace transform technique.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Besides the above authors, Ersoy has reported excellent results for different fluid flows induced by eccentric-concentric rotation of a disk and the fluid at infinity for both Newtonian (Ersoy 2003) and non-Newtonian fluids, e.g. second-grade fluid and Maxwell fluid (Ersoy 2010, 2014). Similar to the previous authors, Ersoy (2003, 2010, 2014) have also investigated these problems using the Laplace transform technique.…”
Section: Introductionmentioning
confidence: 96%
“…second-grade fluid and Maxwell fluid (Ersoy 2010, 2014). Similar to the previous authors, Ersoy (2003, 2010, 2014) have also investigated these problems using the Laplace transform technique.…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate boundary conditions for the velocity field are We shall suppose that the extra stress tensor S depends only on z (see [25]). Using Eqs.…”
Section: Basic Equations and Solutionmentioning
confidence: 99%
“…The aim of this paper is to extend the study considered in [25] to the magnetohydrodynamic flow. The results obtained for the velocity field are presented graphically in terms of the Deborah number, the suction/injection velocity parameter, the Reynolds number, and the Hartmann number.…”
Section: Introductionmentioning
confidence: 99%
“…Since no single model can describe all the complex properties of non-Newtonian fluids, a variety of models are presented in the literature for investigating various properties and behaviors of non-Newtonian fluids. [1][2][3][4][5][6][7] Among them, viscoelastic Oldroyd-B fluid models, which can foresee stress relaxation, have obtained much consideration. Many researchers are paying attention toward this model as it best describes the fluid with viscoelastic properties.…”
Section: Introductionmentioning
confidence: 99%